Revisiting the Inscrutable Granular Cell Tumors in the Breast and Beyond: An Institutional Experience - Nayanatara Swamy; Patrick Jennings; Rachel Taylor; Scott B Harter; Asangi R Kumarapeli; Gwendolyn Bryant-Smith (Archives of Breast Cancer, 2022)
Background: Granular cell tumors (GrCTs) are rare neoplasms derived from Schwann cells and can affect any part of the body. They are histologically categorized into benign (most common), atypical, or malignant (<2%) subtypes. Methods: A retrospective review of pathology-proven GrCTs at a tertiary hospital was done from 4/1/2014 to 3/31/2021. The patient age, gender, location of the tumor, and imaging findings were reviewed. Results: A total of 18 patients with GrCTs were found over a period of 7 years. The sites of involvement ranged from the tongue to the heel. The most common site of occurrence was the esophagus. There were 2 cases of recurrences and 2 cases of multicentric GrCTs. In our study, we did not have atypical or malignant GrCTs. Conclusion: Granular cell tumors are uncommon and primarily published as case reports and case series. Our seven-year review provides a comprehensive synopsis of this tumor in the breast and rest of the body. Their clinical and imaging features are non-characteristic, but histopathologic features with immunohistochemistry are diagnostic. Complete surgical excision with negative margins is the accepted standard of care. A global overview of this tumor will allow physicians to provide their patients with a better understanding of their diagnosis and prognosis.